OPTIMAL DESIGN AND ANALYSIS OF A DC–DC SYNCHRONOUS CONVERTER USING GENETIC ALGORITHM AND SIMULATED ANNEALING - K.S., Rama Rao; C. K., Chew (ACTA Press, 2009)
This paper presents the application of Genetic Algorithm (GA) and Simulated Annealing (SA) techniques for optimal design and analysis of a DC–DC converter with synchronous rectification normally used in battery charge/discharge circuits in DC uninterruptible power supply systems. Converter models for simulation are designed for the forward and backup modes of operation. The results are analysed and compared to those of the expected ideal operation to confirm the validity of the models. An objective function of the converter efficiency in the forward mode operation is derived based on the steady-state values of simulation model. A constrained optimization on the objective function is performed using GA and SA, and optimal parameters are derived. The design and analysis of the converter are performed using software tools within the MATLAB/SIMULINK environment for GA. The derived optimal parameters of the converter from GA are compared with those obtained with SA technique.